PENGARUH APLIKASI LIMBAH CAIR TEMPE DAN SERASAH DAUN KACANG TANAH TERHADAP PERTUMBUHAN BIBIT TANAMAN KEDELAI (Glycine Max L Merryl) - Suhardjito Suhardjito (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
The purpose of this study was to determine the effect of tempeh liquid waste and peanut leaf extract on the growth of soybean plants (Glycine max L. Merril). The study was conducted on 25 cm x 30 cm plots in Kwadungan Lor Village, Padas District, Ngawi Regency. The study was conducted for three months, from July 2025 to September 2025, using a completely randomised design (RAL). The factorial design consisted of two factors and three replications. The first factor, liquid tempeh waste, consisted of 5 levels: T0 = without liquid tempeh waste, water, or 100 tempeh (100 ml of water per plant); T1 = liquid waste with a concentration of 40% per plant; T2 = liquid tempeh waste with a concentration of 60% per plant; T3 = liquid tempeh waste with a concentration of 80% per plant; and T4 = liquid tempeh waste with a concentration of 100% per plant. The second factor, peanut litter (S), consisted of 4 levels: S0 = without peanut leaf litter/plant (5T/Ha); S1 = peanut litter with 5.25 grams per plant (10T/Ha); S2 = peanut leaf litter with 10.50 grams per plant (15T/Ha); S3 = peanut leaf litter with 15.75 grams per plant (20T/Ha); and S4 = peanut leaf litter with 21 grams per plant (25 tons/ha). Each polybag consisted of two soybean seedlings. The parameters observed were plant height, number of leaves, number of productive branches, and number of pods. The results showed that the interaction of 100% tempeh liquid waste per plant and 21 grams of peanut leaf litter per plant on soybeans (Glycine max L. Merryl) resulted in the highest plant height, number of leaves, number of productive branches, and number of pods filled compared to other treatments. Keywords: Tempeh Liquid Waste, Peanut Plant Litter, Soybean Seeds